2006
DOI: 10.1111/j.1813-6982.2006.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Student Characteristics on Achievement in Introductory Microeconomics in South Africa

Abstract: This paper uses OLS regression analysis to examine the effect of student characteristics on performance in Introductory Microeconomics at five South African universities. No consistent race-effects were found, but Indian students performed significantly worse than Whites at historically-White universities. Male students outperformed females in general. Older students did better at the historically-White institutions only. At one university, Black students who speak English as their home language outperformed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 41 publications
5
51
3
Order By: Relevance
“…Among those with no economics background, the oldest age group has the highest economic literacy whereas among those students who have done economics before both older age groups have significantly lower economic literacy than the youngest age group. This non-linear association between economic literacy and age is similar to that observed by Parker (2006) in South Africa. Having a high interest in economics is only significant among those who have studied some economics before, as is reading books on economics and business.…”
Section: No Prior Economicssupporting
confidence: 66%
“…Among those with no economics background, the oldest age group has the highest economic literacy whereas among those students who have done economics before both older age groups have significantly lower economic literacy than the youngest age group. This non-linear association between economic literacy and age is similar to that observed by Parker (2006) in South Africa. Having a high interest in economics is only significant among those who have studied some economics before, as is reading books on economics and business.…”
Section: No Prior Economicssupporting
confidence: 66%
“…However, these results are not universal. Some studies have found no significant gender effect on student performance in economics when course grade is a dependent variable (Kelley, 1975;Buckles & Freeman, 1983;Watts, 1987;Rhine, 1989;Borg & Shapiro, 1996;Parker, 2006;Swope & Schmitt, 2006). These diverging findings may be due to the fact that gender groups are mutually heterogeneous when it comes to personality types of students in a business school.…”
mentioning
confidence: 72%
“…Student effort devoted to learning has been interpreted in different ways and with mixed results in the educational production function (Parker, 2006). Some studies use attendance at lectures as a proxy for student effort (Romer, 1993;Durden and Ellis, 1995;Stratford and Sulock, 1995;Marburger, 2001).…”
Section: Independent Variablesmentioning
confidence: 99%
“…Competence in mathematics and physical science is generally found to be strongly associated with performance in economics at least (Van Walbeek 2004;Parker 2006;Smith and Edwards 2007;Smith 2009). Dummy variables for each of these school-leaving subjects are included.…”
Section: Specificationmentioning
confidence: 99%